Diagnosis of myocarditis: Current state and future perspectives. (15th July 2015) - Biesbroek, P. Stefan; Beek, Aernout M.; Germans, Tjeerd; Niessen, Hans W.M.; van Rossum, Albert C.
Abstract: Myocarditis, i.e. inflammation of the myocardium, is one of the leading causes of sudden cardiac death (SCD) and dilated cardiomyopathy (DCM) in young adults, and is an important cause of symptoms such as chest pain, dyspnea and palpitations. The pathophysiological process of disease progression leading to DCM involves an ongoing inflammation as a result of a viral-induced auto-immune response or a persisting viral infection. It is therefore crucial to detect the disease early in its course and prevent persisting inflammation that may lead to DCM and end-stage heart failure. Because of the highly variable clinical presentation, ranging from mild symptoms to severe heart failure, and the limited available diagnostic tools, the evaluation of patients with suspected myocarditis represents an important clinical dilemma in cardiology. New approaches for the diagnosis of myocarditis are needed in order to improve recognition, to help unravel its pathophysiology, and to develop new therapeutic strategies to treat the disease. In this review, we give a comprehensive overview of the current diagnostic strategies for patients with suspected myocarditis, and demonstrate several new techniques that may help to improve the diagnostic work-up. Highlights: EMB and CMR form the backbone of the current diagnostic work-up of patients with suspected myocarditis. The diagnostic assessment of EMB samples should include histopathology, immunohistochemistry, and viral PCR. CMR allows for the diagnosis of myocarditis, and can be used to differentiate between other causes of cardiomyopathy. The diagnosis of myocarditis remains challenging as a result of the diverse clinical presentation and the drawbacks of EMB and CMR New diagnostic tools are being developed that may complement and improve on current diagnostic approaches for myocarditis.